2019
DOI: 10.1007/s00122-019-03335-y
|View full text |Cite
|
Sign up to set email alerts
|

CLAVATA signaling pathway genes modulating flowering time and flower number in chickpea

Abstract: Key message A combinatorial genomic strategy delineated functionally relevant natural allele of a CLAVATA gene and its marker (haplotype)-assisted introgression led to development of the early-flowering chickpea cultivars with high flower number and enhanced yield/productivity. Abstract Unraveling the genetic components involved in CLAVATA (CLV) signaling is crucial for modulating important shoot apical meristem (SAM) characteristics and ultimately regulating diverse SAM-regulated agromorphological traits in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…In A. thaliana a mutation of the homolog of this gene ( At1G65380 ) causes altered flower development, late flowering or interrupted flowering caused by a temporary termination of the main inflorescence flower meristem (TAIR, 2019c). In a recent paper, Basu et al (2019) identified four Clavata genes, including Clavata2 , that are highly associated with days to flowering in Cicer arietinum L.…”
Section: Discussionmentioning
confidence: 99%
“…In A. thaliana a mutation of the homolog of this gene ( At1G65380 ) causes altered flower development, late flowering or interrupted flowering caused by a temporary termination of the main inflorescence flower meristem (TAIR, 2019c). In a recent paper, Basu et al (2019) identified four Clavata genes, including Clavata2 , that are highly associated with days to flowering in Cicer arietinum L.…”
Section: Discussionmentioning
confidence: 99%
“…Flowering time plays a crucial role in crops’ adaptations and yield stabilisations in response to environmental cues [ 14 , 15 , 16 ]. Physiological studies have shown that salinity delays flowering time and severely affects the pod filling stages [ 9 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor WRKY71 accelerates flowering via the direct activation of the flowering time integrator gene FLOWERING LOCUS T and the floral meristem identity genes LEAFY ( Yu et al, 2016 ). The CLAVATA gene is also reported to modulate flowering time and flower number in chickpeas ( Basu et al, 2019 ). We also identified several genes homologous to A. thaliana CONSTANS-like gene COL9 , phytochrome gene PHYB1 , histone H3 lysine 27 demethylase gene REF6 (a relative of early flowering 6), and PAS domain gene ADO3 , which were severely repressed during F. graminearum infection at 1 or 3 hpi ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%